5‐ALA‐mediated photodynamic therapy reduces the parasite load in mice infected with Leishmania braziliensis. (March 2017) - Souza, D. M.; Alves, P. M.; Silva, M. L. F.; Paulino, T. P.; Coraspe, H. O.; Mendonça, M. M. S.; Ribeiro, B. M.; da Silva, M. V.; Rodrigues Júnior, V.; Rodrigues, D. B. R.
Summary: Photodynamic therapy (PDT) has proven to be an effective alternative for the treatment of cutaneous leishmaniasis. Skin lesions consist of ulcers with well‐defined raised edges, and granular floor. Th1 immune response is the protective profile in patients infected with Leishmania . In this study, the photodynamic therapy with 5‐aminolevulinic acid, the parasitic load, and the modulation of the immune response was evaluated in mice infected with Leishmania braziliensis . Balb/c mice were infected with L. braziliensis and subsequently treated with three sections of PDT. The parasite load and mRNA expression of cytokines (IFN‐γ, IL‐4, IL‐17, IL‐22, IL‐27, IL‐10) and transcription factors (GATA‐3, Foxp3 and T‐bet) were analysed by quantitative PCR. The parasite load in the treated group was significantly lower than in the untreated group ( P <.0001); in PDT treated animals, we observed an increase in IFN‐γ and T‐bet mRNA ( P =.012 and P =.0071). There was a significant reduction in mRNA expression of IL‐22 associated with an increased expression of IL‐27 mRNA in the animals treated with light only ( P =.0001). 5‐ALA associated with photodynamic therapy promotes a reduction in parasite load and an increased expression of IFN‐γ and T‐bet mRNA.